The Causes of Unemployment in Interwar Australia - Dimsdale, N; Horsewood, N (Department of Economics (University of Oxford), 2001)
This paper examines the factors contributing to the rise in unemployment in Australia during the depression of the 1930s and to its decline in the subsequent recovery. While previous writers have generally argued that demand side variables were predominant, it has also claimed that excessive real wages created unemployment. The Layard-Nickell model, which has been used to examine the relationship between real wages and unemployment in interwar Britain, is estimated from Australian data. The results of the estimation confirm that demand side variables in the form of changes in government spendin g and in the terms of trade were important in both the downturn and the recovery. Although real wages affected employment and wage indexation procedures resulted in some real wage rigidity this was not a major contributor to unemployment. In addition wage indexation resulted in a high degree of flexibility of money wages, so that nominal inertia was not a problem. This is in contrast to a country, such as the UK, where wages are determined by collective bargaining rather than by formal wage regulation. No evidence was found that the much discussed decision of the Commonwealth Court to reduce real wages by 10% was effective.